Differences in evidence-based osteoporosis medication use between elderly men and women enrolled in Medicare Part D. Issue 2 (5th March 2019) - Loh, Feng-Hua Ellen; Stuart, Bruce; Davidoff, Amy; Sturpe, Deborah; Onukwugha, Eberechukwu; Hochberg, Marc
Abstract: Objective: To compare osteoporosis treatment utilization rate between elderly men and women. Methods: Cross-sectional and panel analyses of Medicare beneficiaries (1) aged 70 years and older, (2) enrolled in Part A, B and Part D stand-alone prescription drug plans from 1 January 2006 through 31 December 2008, or death, and (3) diagnosed of osteoporosis drawn from a random 5% sample of the Medicare population. Prescription drugs used to treat osteoporosis included bisphosphonates, calcitonin, parathyroid hormone analog and selective estrogen receptor modulator. Covariates included demographic characteristics, conditions and medications contributing to osteoporosis, bone fracture, or falls, contraindication and side effects of osteoporosis medications captured from Medicare claims. Key findings: The study sample comprised 8465 men and 90 956 women with osteoporosis. Prevalence of osteoporosis medication use in men was substantially less than for women (25.2% versus 44.3% in 2006). With advancing age, men were more likely to be treated than women. Black men and women were much less likely (RR 0.76, 95% CI (0.68, 0.85) for men; RR 0.61, 95% CI (0.59, 0.63) for women) to be treated for osteoporosis compared to white men and women. Men who received BMD testing were much more likely to be treated compared to women. Bisphosphonates were the treatment of choice for both men and women, with nonbisphosphonate use increasing with advancing age. Conclusion: Elderly men are significantly undertreated for osteoporosis compared to elderly women, and this is particularly problematic among blacks.